Medusae (Scyphozoa and cubozoa) from southwestern atlantic and subantarctic region (32-60°s, 34-70°W): Species composition, spatial distribution and life history traits - Schiariti, Agustin (2018)
In this study, we reported the species composition and spatial distribution of Scyphomedusae and Cubomedusae from the southwestern Atlantic and Subantarctic region and reviewed the available knowledge of life history traits of these species. We gathered the literature records and presented new information collected from oceanographic and fishery surveys carried out between 1981 and 2017, encompassing an area of approximately 6,7 million km2 (32-60°S, 34-70°W). We confirmed the occurrence of 15 scyphozoans and 1 cubozoan species previously reported in the region. Lychnorhiza lucerna and Chrysaora lactea were the most numerous species, reaching the highest abundances/biomasses during summer/autumn period. Desmonema gaudichaudi, Chrysaora plocamia, and Periphylla periphylla were frequently observed in low abundances, reaching high numbers only occasionally. Phacellophora camtschatica, Aurelia sp., Drymonema gorgo, Atolla chuni, Stygiomedusa gigantea and Pelagia cf. noctiluca were observed always in low numbers. Atolla wyvillei, Stomolophus meleagris, Desmonema comatum and Tamoya haplonema were reported just a few times and mostly individually. Although new species/reports can be found as surveys are undertaken, these results are considered to be the reliable baseline for further ecological studies seeking to understand the ecological role that these jellyfish play in marine ecosystems.